2020
DOI: 10.3390/su12083112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Earthworm Cast Application on Water Evaporation and Storage in Loess Soil Column Experiments

Abstract: Earthworm cast is a common bio-organic fertiliser, which can effectively improve soil fertility and structure. However, only a few studies have focused on the effect of earthworm cast on soil water movement. In this study, loess soil was used to determine the effects of earthworm cast application on soil evaporation. The effects on water storage capacity and capillary upward movement were also investigated. A laboratory-based soil column experiment using earthworm cast with different particle sizes (1–3 × 1–2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Earthworm casts are rich in organic matter content and have good water retention and air permeability. Li et al (2020) found that earthworm casts can reduce water evaporation and improve soil water retention. Bottinelli et al (2010) reported that endogeic earthworms can produce approximately five‐fold casts of their own weight per day.…”
Section: Discussionmentioning
confidence: 99%
“…Earthworm casts are rich in organic matter content and have good water retention and air permeability. Li et al (2020) found that earthworm casts can reduce water evaporation and improve soil water retention. Bottinelli et al (2010) reported that endogeic earthworms can produce approximately five‐fold casts of their own weight per day.…”
Section: Discussionmentioning
confidence: 99%
“…The SWC of the earthworm-treated soils was significantly greater than that of the C (p < 0.05)) in the surface 0-20 cm of soil. The averages of the SWC were in decreased order with the earthworm density in all the experiment times, namely, HDE > MDE > LDE > C. Li et al [30] suggested that earthworm casts are a natural water-retaining material. The majority of studies consider that the casts of earthworms are better water stabilizing aggregate [38].…”
Section: Impact Of Earthworms On Swcmentioning
confidence: 93%
“…The result is similar to that obtained by Wang [40], who showed that mulch treatment can effectively regulate soil temperature. Li et al [30] also suggested that aggregates of earthworms could form a new soil layer that positively reduces evaporation. During this experiment, the HDE (1422.6 g) had more casts than the MDE (871.8 g) and the LDE (543.6 g) mulching on the soil surface.…”
Section: Impact Of Earthworm On Temperature and Evaporationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have reported that earthworms can have important influences on physical and biological effects that affect the nutrient supply to plants, therefore improving plant growth [22,[28][29][30][31][32]. Earthworms are also known to contribute to the aggregate stability of soils varying in texture, carbonate and concentration of organic matter by burrowing, foraging and casting on the soil surface and within the soil [33][34][35][36][37]. It has been proved that earthworm could modify the structure, microbial activity and nutrient mineralization in soils [12,[38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%